(untitled) (Marketing Journal, 2024)
Manufacturing enterprises of the textile and light industry of Uzbekistan are a large diversified production complex with a high level of equipment. These enterprises are able to supply a wide range of products to foreign markets, from yarns to finished products. Modern design and high quality indicators ensure the competitiveness of products and allow them to take their rightful place in the international market.